2014
DOI: 10.3109/02699206.2013.874040
|View full text |Cite
|
Sign up to set email alerts
|

Changes in voice onset time and motor speech skills in children following motor speech therapy: Evidence from /pa/ productions

Abstract: This study evaluated changes in motor speech control and inter-gestural coordination for children with speech sound disorders (SSD) subsequent to Prompts for Restructuring Oral and Muscular Phonetic Targets (PROMPT) intervention. We measured the distribution patterns of voice onset time (VOT) for a voiceless stop (/p/) to examine the changes in inter-gestural coordination. Two standardized tests were used (Verbal Motor Production Assessment for Children (VMPAC), GFTA-2) to assess the changes in motor speech sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
0
19
0
4
Order By: Relevance
“…However, singing shows a major benefit for adolescents who stutter in reducing VOT variability which was not observed in adolescents who do not stutter. In spoken speech, it is known that individuals who stutter produce more variable VOTs compared to controls, indicating less efficient or mature motor control processes (Whiteside et al, 2003;Yu et al, 2014). In the present study, singing also produced advantages for articulatory stability in adolescents who do not stutter, notably, by generating smaller vowel and utterance variability in sung productions.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, singing shows a major benefit for adolescents who stutter in reducing VOT variability which was not observed in adolescents who do not stutter. In spoken speech, it is known that individuals who stutter produce more variable VOTs compared to controls, indicating less efficient or mature motor control processes (Whiteside et al, 2003;Yu et al, 2014). In the present study, singing also produced advantages for articulatory stability in adolescents who do not stutter, notably, by generating smaller vowel and utterance variability in sung productions.…”
Section: Discussionmentioning
confidence: 44%
“…It has therefore been assessed in developmental studies as well as in studies of speech disorders (Auzou et al, 2000;Whiteside, Dobbin, & Henry, 2003;Yu et al, 2014;Yu, De Nil, & Pang, 2015). In particular, VOT variability has been discussed as a marker of fine-grained motor and timing control of oral and laryngeal processes.…”
Section: Introductionmentioning
confidence: 98%
“…The study reported improvements on all speech measures; however, the study design did not include experimental control measures (essentially a one-group pre-post design), and as such it cannot be concluded that any improvements were attributable to the intervention. A number of additional studies have examined PROMPT intervention in children with motor speech disorders, with sample sizes ranging from N=5 to N=12, although all of these studies explicitly excluded children with CAS [8688]. Further, only one of these studies [87] used a design with experimental control measures, rather than uncontrolled pre-post designs which cannot support claims of efficacy.…”
Section: Motor-based Treatment Approachesmentioning
confidence: 99%
“…To the best of our knowledge, VOT was rarely used to study the motor control ability of children with FAD [28][29][30]. Previous studies [21] measured the VOT of the stop consonants /d/ and /t/ produced by subjects with ataxic dysarthria, finding that the patient group reduced categorical distinction between the VOT of voiced stop consonants and unvoiced stop consonants.…”
Section: Discussionmentioning
confidence: 99%